Rethinking antifascism : history, memory and politics, 1922 to the present - García, Hugo, 1975-; Yusta Rodrigo, Mercedes; Tabet, Xavier; Clímaco, Cristina, 1965- (New York : Berghahn Books, 2016)
Bringing together leading scholars from a range of nations, Rethinking Antifascism provides a fascinating exploration of one of the most vibrant sub-disciplines within recent historiography. Through case studies that exemplify the field's breadth and sophistication, it examines antifascism in two distinct realms: after surveying the movement's remarkable diversity across nations and political cultures up to 1945, the volume assesses its postwar political and ideological salience, from its incorporation into Soviet state doctrine to its radical questioning by historians and politicians. Avoiding both heroic narratives and reflexive revisionism, these contributions offer nuanced perspectives on a movement that helped to shape the postwar world.
Introduction : Beyond Revisionism : Rethinking Antifascism in the Twenty-First Century / Hugo García, Mercedes Yusta, Xavier Tabet, Cristina Clímaco -- Freedom for Thälmann! The Comintern and the Orchestration of the Campaign to Free Ernst Thälmann, 1933-39 / Anson Rabinbach -- Was the French Popular Front Antifascist? / Michael Seidman -- "Beyond Cable Street" : New Approaches to the Historiography of Antifascism in Britain in the 1930s / Tom Buchanan -- Searching for Antifascism: Historiography, the Crisis of the Liberal State and the Birth of Fascism and Antifascism in Italy, Spain and Portugal / Giulia Albanese -- Was there an Antifascist Culture in Spain during the 1930s? / Hugo García -- Portugal within the European Antifascist Movement, 1922-39 / Cristina Clímaco -- The Argentine Antifascist Movement and the Building of a Tempting Domestic Appeal, 1922-46 / Andrés Bisso -- Women and Antifascism : Historiographical and Methodological Approaches / Isabelle Richet -- The Strained Courtship between Antifascism and Feminism: from the Women's World Committee (1934) to the Women's International Democratic Federation (1945) / Mercedes Yusta -- From Antifascistas to PAF : Lexical and Political Interpretations of American International Brigaders in Spain and World War II / Robert S. Coale -- An Antifascist Political Identity? : On the Cult of Antifascism in the Soviet Union and post-Socialist Russia / José María Faraldo -- The Burden of the Rear-view Mirror: Myth and Historiography of Republican Antifascism in France / Gilles Vergnon -- Did Revisionism Win? : Italy between Loss of Historical Consciousness and Nostalgia for the Past / Stéphanie Prezioso -- Antifascism and the Resistance : Public Debates and Politics of Memory in Italy from the 1990s to Today / Filippo Focardi -- In Search of the Lost Narrative : Antifascism and Democracy in Present Day Spain / Javier Muñoz Soro -- Dictatorship and Revolution : Disputes over Collective Memory in Post-Authoritarian Portugal / Manuel Loff and Luciana Soutelo -- Antifascism between Collective Memory and Historical Revisions / Enzo Traverso.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Anti-fascist movements -- History; Antifascisme -- Histoire; POLITICAL SCIENCE -- Essays; POLITICAL SCIENCE -- Government -- General; POLITICAL SCIENCE -- Government -- National; POLITICAL SCIENCE -- Reference; POLITICAL SCIENCE -- Political Ideologies -- Fascism & Totalitarianism; Anti-fascist movements; History